Marketing de relacionamento e a qualidade da relação entre discentes e a Universidade de Passo Fundo - Rosa, Karolaine Segatto da (2023)
Relationship Marketing has become increasingly present and important for companies over the years. It is an excellent strategy to develop and improve the way to retain and retain the customer through a lasting and prosperous relationship. Since with the wide competition in the market and the increase in technology, consumer choices are increasingly demanding, seeking to meet their demands in the best possible way. For this reason, the purpose of this article is to analyze the level of relational quality between the UPF and the students of the Administration and Accounting courses at the Soledade-RS campus. For this, bibliographies and Descriptive Quantitative research were used as a study method through an online questionnaire applied to students of the Administration and Accounting classes. Therefore, it was possible to raise a promising analysis regarding the results obtained. In summary, the present study achieved its purpose and how contribution, it endorses future analysis and deepening of this content.